2021
DOI: 10.3389/fmed.2021.592336
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19 Hospital Length of Stay and Risk of Death Using Artificial Intelligence-Based Modeling

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly infectious virus with overwhelming demand on healthcare systems, which require advanced predictive analytics to strategize COVID-19 management in a more effective and efficient manner. We analyzed clinical data of 2017 COVID-19 cases reported in the Dubai health authority and developed predictive models to predict the patient's length of hospital stay and risk of death. A decision tree (DT) model to predict COVID-19 length of stay was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Similar to our findings, Alwafi et al reported that hospitalized COVID-19 patients with end-stage renal diseases had a significantly higher risk of mortality and a significantly prolonged LoHS [ 13 ]. Mahboub et al found that diagnosis at admission, painkiller usage, ventilator intubation, azithromycin usage, antiviral usage, anti-inflammatory agent usage, vitamin C usage, urea test results, platelet count, haemoglobin levels, dimer levels, and potassium levels were significant predictors of LoHS [ 39 ]. Moreover, Wang et al reported that age and clinical grade were strongly related to the length of stay ( p < 0.01) and that a longer LoHS was associated with ≥45 years of age, severe illness, and admission to a provincial hospital [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Alwafi et al reported that hospitalized COVID-19 patients with end-stage renal diseases had a significantly higher risk of mortality and a significantly prolonged LoHS [ 13 ]. Mahboub et al found that diagnosis at admission, painkiller usage, ventilator intubation, azithromycin usage, antiviral usage, anti-inflammatory agent usage, vitamin C usage, urea test results, platelet count, haemoglobin levels, dimer levels, and potassium levels were significant predictors of LoHS [ 39 ]. Moreover, Wang et al reported that age and clinical grade were strongly related to the length of stay ( p < 0.01) and that a longer LoHS was associated with ≥45 years of age, severe illness, and admission to a provincial hospital [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, stochastic modeling was previously used to model the human immune response to the yellow fever vaccine ( 9 ). Since COVID-19 is linked to immune response, modeling of the SARS-CoV-2 infection have been extensively published on different aspects of the disease, including the immune system using multiple ODEs to model immune cells, antibodies and cytokines ( 10 13 ), and on the clinical and radiological data ( 14 16 ). A few models on cytokine release syndrome in other diseases were also created ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…From a management point of view, research in Dubai used AI-based modeling by using Decision Tree prediction models to forecast the LoS and risk of mortality accurately. In principle, these smart models might equip front-line clinicians with the tools they need to improve management techniques and save lives [ 19 ].…”
Section: Introductionmentioning
confidence: 99%